Factors Related to Fe Tablet Consumption Compliance among Pregnant Women in The Work Area of Pasir Jaya Health Centre Tangerang District - Rukmaini; Fitriawati; Azzahroh, Putri (Rajaki of Tulip Medika Publisher, 2023)
Background: The prevalence of anemia in pregnant women in Indonesia is 70%, or 7 out of 10 pregnant women suffer from anemia. The low adherence of pregnant women in taking iron supplements is one of the reasons the prevalence rate of anemia is still high. Purpose: To determine the factors related to compliance with consumption of Fe tablets in pregnant women in the work area of ​​the Pasir Jaya Health Center, Tangerang Regency in 2022 Methods: The research design used is descriptive correlation. This research uses the Cross Sectional method. The number of samples or respondents is 77 respondents with the Simple Random Sampling technique. Result: The results of the study showed that of the 77 respondents used as the research sample, the results obtained were that 27 respondents had non-compliant compliance criteria with a percentage of 35.1%, and 50 respondents had compliance criteria with a percentage of 64.9%. There is a relationship between knowledge and non-compliance with the sig value. of 0.046, there is a relationship between perception and compliance with the sig value. of 0.018, there is a relationship between family/husband support and compliance with the sig. of 0.016, and there is no relationship between the support of health workers and adherence to the sig. of 0.836. Conclusions: It is recommended that pregnant women adhere to consuming iron tablets during pregnancy and know the consequences if they are not consumed properly. Iron tablets that have been given by health workers.